The pathophysiology of osteoporosis in obesity and type 2 diabetes in aging women and men: The mechanisms and roles of increased bone marrow adiposity - Ali, Dalia; Tencerova, Michaela; Figeac, Florence; Kassem, Moustapha; Jafari, Abbas (Frontiers in Endocrinology, 2022)
Osteoporosis is defined as a systemic skeletal disease characterized by decreased bone mass and micro-architectural deterioration leading to increased fracture risk. Osteoporosis incidence increases with age in both post-menopausal women and aging men. Among other important contributing factors to bone fragility observed in osteoporosis, that also affect the elderly population, are metabolic disturbances observed in obesity and type 2 diabetes (T2D). These metabolic complications are associated with impaired bone homeostasis and a higher fracture risk. Expansion of the bone marrow adipose tissue (BMAT), on the expense of decreased bone formation, is thought to be one of the key pathogenic mechanisms underlying osteoporosis and bone fragility in obesity and T2D. Our review provides a summary of mechanisms behind increased bone marrow adiposity (BMA) during aging and highlights the pre-clinical and clinical studies connecting obesity and T2D, to BMA and bone fragility in aging osteoporotic women and men.